Mid-infrared femtosecond laser-induced damages in As2S3 and As2Se3 chalcogenide glasses - Chenyang You (Nature Portfolio, 2017)
Abstract In this paper, we report the first measurements of mid-infrared (MIR) femtosecond laser-induced damage in two typical chalcogenide glasses, As2S3 and As2Se3. Damage mechanism is studied via optical microscopy, scanning electron microscopy and elemental analysis. By irradiating at 3, 4 and 5 μm with 150 fs ultrashort pulses, the evolution of crater features is presented with increasing laser fluence. The dependence of laser damage on the bandgap and wavelength is investigated and finally the laser-induced damage thresholds (LIDTs) of As2S3 and As2Se3 at 3 and 4 μm are calculated from the experimental data. The results may be a useful for chalcogenide glasses (ChGs) applied in large laser instruments to prevent optical damage.